(3bGfhf GdJChjds - (3eMeO Hf YHO Gddg Hf eMeO GdeYGaQj GdETHjdj GdeGdcj, GdbGVj CHh HcQ GHf GdYQHqj , J (B543 (3g` s
(3ChdgG (B:s
(3jHOC GdehLhO efg HPcQ GHJOGA WdH GdYde s
(3BNQgG (B:s
(3hbaI cGJH CKfGA (B" (3GSJjaGA GdZQV ai GdJbSje (B" (3Hbhdg (B: (3hJHjf dc Cf eYQaI GdQH Jchf HGdYe hcJH CRGAg ai GdgGeS gPG eG hLOfGg ai GdCe (B[ (3Ci ai GdCUd GdefJSN efg (B] s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B230s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3GdJaSjQ hYdhe GdbQBfs